Occupational biopsychosocial factors associated with neck pain intensity, neck-disability, and sick leave: A cross-sectional study of construction labourers in an African population. - Chinonso N Igwesi-Chidobe; Excellence Effiong; Joseph O Umunnah; Benjamin C Ozumba (PLoS ONE)
Introduction The burden and impact of neck pain is high in African countries including Nigeria. This study investigated the occupational biomechanical and occupational psychosocial factors associated with neck pain intensity, neck disability and sick leave amongst construction labourers in an urban Nigerian population. Methods This cross-sectional study measured clinical neck pain outcomes, occupational biomechanical factors, and occupational psychosocial factors. Descriptive, and univariate/multivariate inferential statistical analyses were conducted. Results Significant independent factors associated with neck pain intensity were order and pace of tasks being dependent on others (β = 0.35; p<0.0001); inability to take breaks in addition to scheduled breaks (β = 0.25; p<0.0001); inability to work because of unexpected events (β = 0.21; p<0.0001); inability to control the order and pace of tasks (β = 0.20; p<0.0001); and weight of load (β = 0.17; p<0.0001); accounting for 53% of the variance in neck pain intensity. Significant independent factors associated with neck disability were weight of load (β = 0.30; p<0.0001); duration of load carriage (β = 0.16; p = 0.01); working under time pressure/deadlines (β = 0.16; p = 0.02); and accounting for 20% of the variance in neck disability. Significant independent factor associated with sick leave was duration of load carriage (β = 0.15; p = 0.04), in a non-significant regression model explaining -4% of the variance in sick leave. Addition of pain intensity significantly explained more variance in neck disability (31.0%) but less variance in sick leave (-5%), which was not statistically significant (F (10, 190) = 0.902, p = 0.533). Conclusions Occupational biomechanical factors may be more important than occupational psychosocial factors in explaining neck disability and sick leave. In contrast, occupational psychosocial factors may be more important than occupational biomechanical factors in explaining neck pain intensity in this population in Nigeria.